2022
DOI: 10.3390/children9040520
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Types of Social Supports and Their Association with Mental Health Symptoms and Life Satisfaction among Young Adults with a History of Out-of-Home Care

Abstract: Young adults with a history of out-of-home care report poorer mental health and life satisfaction compared to non-care-experienced peers. Social support is a known protective factor for mental health. There is limited evidence, however, on the relationship between sources (e.g., family members) and types (e.g., information) of social support and mental health symptoms and life satisfaction in this population. Reporting cross-sectional survey data from 215 young adults aged 18–22 years with a history of out-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…FHF enrolled 91% of all eligible children at this baseline interview. For more details on the FHF design, including other studies using these data, see Combs et al, 2022;Evans et al, 2022;Taussig & Roberts, 2022. The young adult interview, which is the focus of this study, occurred an average of 9.4 years after the baseline interview and 88.5% of those eligible were located and agreed to participate in a follow-up interview. The follow-up interview, conducted with 206 young adults, included a list of qualitative questions.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…FHF enrolled 91% of all eligible children at this baseline interview. For more details on the FHF design, including other studies using these data, see Combs et al, 2022;Evans et al, 2022;Taussig & Roberts, 2022. The young adult interview, which is the focus of this study, occurred an average of 9.4 years after the baseline interview and 88.5% of those eligible were located and agreed to participate in a follow-up interview. The follow-up interview, conducted with 206 young adults, included a list of qualitative questions.…”
Section: Participantsmentioning
confidence: 99%
“…FHF enrolled 91% of all eligible children at this baseline interview. For more details on the FHF design, including other studies using these data, see Combs et al, 2018; Evans et al, 2022; Taussig & Roberts, 2022 .…”
Section: Participantsmentioning
confidence: 99%
“…Social support can mitigate the long-term negative consequences associated with child maltreatment, protecting against mental illness and suicidal behavior (Evans et al, 2022 ; Katz & Geiger, 2020 ; Kleiman & Liu, 2013 ). However, youth involved in the CW system often report low levels of support from both family and peers (Negriff et al, 2015 ; Pepin & Banyard, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue features 18 articles that examine family risk and resilience among children and adolescents across developmental stages, ranging from early childhood to late adolescence/young adulthood. A wide range of child outcomes are examined in these studies, including children’s use of electronic devices [ 1 , 2 ], maltreatment experiences [ 3 ], mental health [ 4 , 5 , 6 , 7 ], school readiness and academic functioning [ 8 ], suicidal thoughts and behaviors [ 9 ], socioemotional development [ 10 , 11 , 12 , 13 ], and resilient/adaptive functioning [ 14 , 15 , 16 ].…”
mentioning
confidence: 99%
“…In line with Kobulsky et al’s study—but focusing on low-income Hispanic families and their young children during the COVID-19 pandemic—Cabrera et al found that positivity (e.g., staying optimistic about the future) and economic support (e.g., WIC/SNAP) buffered the adverse effects of economic risk and helped parents to manage their parenting stress and stay engaged with their children [ 11 ]. Notably, Evans et al found that having family support and material support predicted greater life satisfaction among youths with a history of out-of-home care; highlighting the importance of both relational and material resources as important family protective factors [ 5 ].…”
mentioning
confidence: 99%